2015
DOI: 10.1093/eurheartj/ehv135
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with cardiac implants protected against electromagnetic interference in daily life and occupational environment?

Abstract: Utilization of cardiac implants such as pacemakers and implantable cardioverter defibrillators is now commonplace among heart disease patients. The ever-increasing technological complexity of these devices is matched by the near omnipresent exposure to electric, magnetic, and electromagnetic fields (EMFs), both in everyday life and the occupational environment. Given that electromagnetic interferences (EMIs) are associated with potential risk in device patients, physicians are increasingly confronted with mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
0
20
0
12
Order By: Relevance
“…Cardiovascular implantable electronic devices vary according to electrode polarity (unipolar or bipolar) [24,25], where the poles (anode and cathode) in the bipolar type were closer together than in the unipolar type [24]. This will lead to reduction in the probability of interpreting extremal signals as a cardiac event(s) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular implantable electronic devices vary according to electrode polarity (unipolar or bipolar) [24,25], where the poles (anode and cathode) in the bipolar type were closer together than in the unipolar type [24]. This will lead to reduction in the probability of interpreting extremal signals as a cardiac event(s) [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been publicly available for more than 15 years and comprises currently 23,800 publications (November 2016). The EMF-Portal is used by scientists (e.g., [2123]), government agencies (e.g., [24]), and academies of science (e.g., [25]). Relevant studies for inclusion in the EMF-Portal are identified on a daily basis with the aid of systematic search strategies in major literature databases such as Pubmed (years of coverage: 1946 to present), Cochrane Library (years of coverage: 1992 to present), and IEEE Xplore Digital Library (years of coverage: 1892 to present).…”
Section: Methodsmentioning
confidence: 99%
“…There are scientific studies on the negative effects of electromagnetic radiation on health. Studies report that the operation of cardiac pacemakers is impaired or completely stopped under electromagnetic radiation and serious health problems occurred or triggered [18,19]. This suggests that monitoring the spectrum is a necessity, especially in the areas where hospitals and healthcare professionals provide healthcare.…”
Section: Impact On Healthmentioning
confidence: 99%